Evaluation of Mangalarga Marchador foal development in the first year of life - Cunha, Ligia Amaral; Sodré, Ticiane d’El Rei Passos; Pereira Neto, Evandro; Souza, Vinicius Ricardo Cuña de; Hunka, Monica Miranda; Manso Filho, Hélio Cordeiro; Coelho, Clarisse Simões (Brazilian Journal of Veterinary Research and Animal Science, 2022)
The purpose of this study was to examine the development pattern of Mangalarga-Marchador foals by determination of muscle development and deposition of adipose tissue associated with the evaluation of blood-based biomarkers. Thus, 72 Mangalarga Marchador foals (ages ranged from 1-12 mo) were randomly selected and divided into 12 age groups (n=6 per group), evaluated monthly. The thickness of the Longissimus dorsi (LD) and rump fat (RF) were determined through an ultrasound performed on each foal’s left side. Such parameters were used to calculate the percentage of body fat (BF), fat mass (FM), and fat-free mass (FFM). Morphometric measurements were taken on the foal’s right side using a tape measure and a hypsometer. Blood samples were collected for determinations of total proteins, albumin, triglycerides, cholesterol, urea, creatinine, and glucose. Morphometric measurements, the thickness of the LD and RF, weight, BF, FM, and FFM showed differences between age groups (P<0.001). Muscle development and fat deposition in subcutaneous tissue were greater between six and 12 months and average weight gain and FFM were proportionally greater between one and six months. We concluded that morphometric measurements increase steadily and linearly during the first 12 months of life, indicating that it is feasible to use the linear regression formula. Moreover, significant differences between age and biochemical biomarkers may be attributed to nutritional and digestive physiology adaptations during these periods.